COVID‐19 pandemic: Practical considerations on the organization of an allergy clinic—An EAACI/ARIA Position Paper. Issue 3 (6th March 2021) - Pfaar, Oliver; Klimek, Ludger; Jutel, Marek; Akdis, Cezmi A.; Bousquet, Jean; Breiteneder, Heimo; Chinthrajah, Sharon; Diamant, Zuzana; Eiwegger, Thomas; Fokkens, Wytske J.; Fritsch, Hans‐Walter; Nadeau, Kari C.; et al.
Abstract: Background: The coronavirus disease 2019 (COVID‐19) has evolved into a pandemic infectious disease transmitted by the severe acute respiratory syndrome coronavirus (SARS‐CoV‐2). Allergists and other healthcare providers (HCPs) in the field of allergies and associated airway diseases are on the front line, taking care of patients potentially infected with SARS‐CoV‐2. Hence, strategies and practices to minimize risks of infection for both HCPs and treated patients have to be developed and followed by allergy clinics. Method: The scientific information on COVID‐19 was analysed by a literature search in MEDLINE, PubMed, the National and International Guidelines from the European Academy of Allergy and Clinical Immunology (EAACI), the Cochrane Library, and the internet. Results: Based on the diagnostic and treatment standards developed by EAACI, on international information regarding COVID‐19, on guidelines of the World Health Organization (WHO) and other international organizations, and on previous experience, a panel of experts including clinicians, psychologists, IT experts, and basic scientists along with EAACI and the "Allergic Rhinitis and its Impact on Asthma (ARIA)" initiative have developed recommendations for the optimal management of allergy clinics during the current COVID‐19 pandemic. These recommendations are grouped into nine sections on different relevant aspects for the care of patients with allergies. Conclusions: This international Position Paper provides recommendations on operational plans and procedures to maintain high standards in the daily clinical care of allergic patients while ensuring the necessary safety measures in the current COVID‐19 pandemic.